Blended Learning in Foreign Language Education - Muna Dalaf (مجلة الآداب, 2022)
In the process of teaching, it can be noticed that instructors can use different ways of information delivery methods to achieve the educational goals that they want to achieve. Various paths can be followed by the instructors when they want to present the information to their students. Whether the method of information delivery is a traditional one, an electronic one, or an approach that blends both of the traditional and the electronic type, the final outcome is the development of the knowledge inside the learners. However, the different ways of information delivery bring with them various advantages and disadvantages. This study is an attempt to give brief information about the blended approach of learning. This study is important since it tries to give brief information for the Iraqi EFL college instructors about this approach. It was not possible to conduct the research empirically because it was done in 2020 when blended learning was applied in Iraqi universities for the first time. An empirical study is recommended to examine college students and instructors’ attitudes towards blended learning and the obstacles they face in its application. . Furthermore, it also remains important the need to establish various workshops that discuss such approach of learning and how to benefit from it